SENYAWA 4-HIDROKSI SINAMAMIDA DARI EKSTRAK ETIL ASETAT (EtOAc) KULIT AKAR PALIASA (Kleinhovia hospita Linn) - Ilyas, Asriani (Teknosains, 2014)
Isolation and identification of secondary metabolites from EtOac extract of the root bark of Kleinhovia hospita Linn. plant had been performed. Separation techniques used consisted of extraction, fractionation, and purification. The compounds obtained were tested and elucidated based on UV, IR, and NMR spectroscopy data. A compound obtained was 4-hydroxy cinnamamide.Keyword : Kleinhovia hospita Linn., 4-hydroxy cinnamamide